Guyanese Women's Experiences of Invisibility in Health Care in England - Mitchell, Helena Ann (Frontiers in Sociology, 2020)
Guyanese women’s experiences of invisibility in health care in England. This article explores the opportunities for strengthening participatory action research (PAR) through an intersectionality framework. In 2015 I completed a PhD study into the lived experiences of migrant Guyanese women, living in England, when seeking diagnoses and treatment for Type 2 diabetes. Group storytelling acted as a lens for the women to talk about how they tried to obtain a diagnosis, in addition to their migratory experiences. Both PAR and intersectionality encourage participant collaboration and community engagement of oppressed groups. The article concludes that the PAR study would have been enhanced by overlaying it with an intersectionality framework. The argument is presented that by doing so the women’s accounts in the research study would have been privileged more and activism encouraged in bringing about change to current practices and avoiding perpetuating existing oppressions. The PhD study methodology was based on Koch’s interpretation of PAR. In this, PAR is used where the focus is on participation of all stakeholders toward reform and change. It is seen as a social, practical and collaborative process where building relationships with participants is crucial. Intersectionality acknowledges the potential for ‘black’ and other women of colour to not remain on the margins but to challenge the traditional biomedical model of health care delivery. Implementing an intersectional approach to the data generation and analysis would have acknowledged power dynamics (i.e. privilege and oppression) and help to identify potential gaps in diabetic provision which are currently invisible or inequitable due to interventions designed to meet the needs of a homogeneous White middle class society.